Acceptance and Use of Muzakki To Pay Non-Cash Zakat in West Java: Theory Extension of Technology of Acceptance Model - Heni Sukmawati; Iwan Wisandani; Mega Rachma Kurniaputri (Universitas Airlangga, 2022)
ABSTRAK Strategi penghimpunan zakat infaq dan sedekah masa kini harus selaras dengan perkembangan teknologi dan perilaku masyarakat 5.0 (society 5.0), dimana Society 5.0 menciptakan masyarakat yang berbasis teknologi sehingga pembayaran zakat, infaq, dan sedekah non tunai harus memanfaatkan teknologi finansial seperti, mobile banking, ATM, QRIS, dompet digital maupun e-commerce. Tujuan penelitian ini yaitu guna mengetahui besarnya penerimaan dan penggunaan layanan teknologi finansial dalam membayar Zakat, Infaq, dan Sedekah (ZIS) menggunakan ekstensi Technology of Acceptance Model (TAM) dengan motivasi spiritual. Adapun metode penelitian yang digunakan adalah Structural Equation Modeling Partial Least Square (SEM-PLS) dengan sebanyak 129 responden yang berasal dari Kota Bekasi, Bandung, Bogor, Cimahi, Sukabumi, Garut, Majalengka, Tasikmalaya, dan Pangandaran. Penelitian ini menemukan bahwa muzakki dalam menerima dan menggunakan layanan teknologi keuangan untuk membayar ZIS secara non tunai dipengaruhi oleh persepsi kemudahan, persepsi kegunaan, sikap, dan intensi. Implikasi dari penelitian ini adalah agar lembaga zakat dapat mengetahui penerimaan dan penggunaan teknologi muzakki dalam menunaikan zakat non tunai sehingga dapat berinovasi dalam menyediakan layanan bagi muzakki maupun masyarakat yang akan membayar zakat non tunai. Kata Kunci: Zakat Non Tunai, Kesejahteraan Umum, Perilaku Mikroekonomi, Ekonomi Keuangan. ABSTRACT The strategy of collecting zakat infaq and alms today must be in line with technological developments and community behavior 5.0 (society 5.0), where Society 5.0 creates a technology-based society. ATM, QRIS, digital wallet, and e-commerce. The purpose of this study is to determine the amount of acceptance and use of financial technology services in paying Zakat, Infaq, and Alms (ZIS) using the Technology of Acceptance Model (TAM) extension with spiritual motivation. The research method used is Structural Equation Modeling Partial Least Square (SEM-PLS) with 129 respondents taken from Bekasi, Bandung, Bogor, Cimahi, Sukabumi, Garut, Majalengka, Tasikmalaya, and Pangandaran. This study found that muzakki in accepting and using financial technology services to pay ZIS non-cash were influenced by perceived ease of use, perceived usefulness, attitudes, and intentions. However, the perceived usefulness does not affect the attitude of muzakki in paying non-cash ZIS, and indirectly the perceived usefulness does not affect the actual use of muzakki to pay ZIS. This research implies that zakat institutions can find out the acceptance and use of muzakki technology in paying zakat so that they can innovate in providing services for muzakki and people who will pay non-cash zakat. Keywords: Non-Cash Zakat, General Welfare, Microeconomic Behavior, Financial Economics. DAFTAR PUSTAKA Aini, Z. N., Yuli, S. B., & Hakim, R. (2018). Perilaku muzakki dalam membayar zakat melalui transaksi non tunai di lembaga inisiatif zakat indonesia (IZI) Surabaya. Iqtishodia, 3(1), 39-58. https://doi.org/10.35897/iqtishodia.v3i1.163 Ajzen, I. (1985). From intentions to actions: A theory of planned behavior. In Action Control (pp. 11-39). Amin, H. (2021). An analysis of online sadaqah acceptance among university graduates in Malaysia. International Journal of Islamic and Middle Eastern Finance and Management. https://doi.org/10.1108/IMEFM-01-2019-0020 Anshari. (1993). Wawasan Islam: Pokok-pokok pikiran tentang Islam dan umatnya. Jakarta: RajaGrafindo Persada. Armitage, C., & Conner, M. (2001). Efficacy of the theory of planned behaviour: A meta-analytic review. British Journal of Social Psychology, 40, 471-499. https://doi.org/10.1348/014466601164939 Asdiansyuri, U. (2016). Analisis pengaruh pengeluaran zakat, infak, dan sedekah terhadap kesejahteraan muzakki. International Journal of Social and Local Economic Governance , 23-31. Astuti, W., & Prijanto, B. (2021). Faktor yang mempengaruhi minat muzaki dalam membayar zakat melalui kitabisa.com: Pendekatan technology acceptance model dan theory of planned behavior. Jurnal Al Muzara'ah, 9(1), 21-45. https://doi.org/10.29244/jam.9.1.21-44 Azman, F. M., & Bidin, Z. (2015). Factors influencing zakat compliance behavior on saving. International Journal of Business and Social Research, 5(1), 118-128. https://doi.org/10.18533/ijbsr.v5i1.688 Baharuddin. (2007). Paradigma psikologi Islami: Studi tentang elemen psikologi dari Al Quran. Yogyakarta: Pustaka Pelajar. BAZNAS. (2021). Outlook zakat Indonesia 2021. Jakarta: Pusat Kajian Strategis BAZNAS. Bidin, Z., Idris, K. M., & Shamsudin, F. M. (2009). Predicting compliance intention on zakah on Employment Income in Malaysia: An Application of Reasoned Action Theory. Jurnal Pengurusan, 28, 85-102. Billah, Z. I. (2016). Analisis pengaruh nilai spiritual zakat terhadap kesejahteraan muzakki melalui perilaku ihsan. Malang: Universitas Islam Negeri Maulana Malik Ibrahim. Chuang, L. M., Liu, C. C., & Kao, H. K. (2016). The Adoption of fintech service: TAM perspective. International Journal of Management and Administrative Sciences, 1-15. DailySocial. (2020). Mengapa masyarakat Indonesia gunakan layanan fintech. Retrieved from https://databoks.katadata.co.id/datapublish/2020/12/28/mengapa-masyarakat-indonesia-gunakan-layanan-fintech Davis, F. D. (1989). Perceived usefulness, perveived ease of use, and user acceptance of information technology. Management Information System Research Center, 319-340. http://dx.doi.org/10.2307/249008 Davis, F. D., Bagozzi, R. P., & Warshaw, P. (1989). User acceptance of computer technology: A comparison of two theoretical models. Management Science, 982-1003. https://doi.org/10.1287/mnsc.35.8.982 Dwilaksono, Y., Handayani, S. D., & Fauziyah. (2018). Effect of usefulness, ease of use, risk, product involvement, and subjective norms to a person's attitude and intentions of using online shopping among students in Yogyakarta. International Journal of Business Quantitative Economics and Applied Management Research, 1-9. Fauzi, A. (2017). Bagaimana hukum membayar zakat secara online. Retrieved from https://money.kompas.com/read/2017/05/16/183000626/bagaimana.hukum.membayar.zakat.secara.online. Ferdinand, A. (2014). Metode penelitian manajemen: Pedoman penelitian untuk penulisan skripsi. tesis, dan disertasi ilmu manajemen. Semarang: Undip Press. Gefen, D., Karahanna, E., & Straub, D. W. (2003). Trust and TAM in online shopping: An integrated model. MIS Quarterly, 27(1), 51-90. https://doi.org/10.2307/30036519 Global Web Index. (2019). E-Commerce in Indonesia. Retrieved from https://datareportal.com/reports/digital-2019-ecommerce-in-indonesia Hair, J., Black, W., Black, B., Babin, B., & Anderson, R. (2010). Multivariate data analysis: Global edition. New York: Pearson. Heikal, & Khaddafi, M. (2014). The intention to pay zakat commercial: An application of revised theory of planned behavior. Journal of Economics and Behavioral Studies, 727-734. Hermanto, S. B., & Patmawati. (2017). Determinan penggunaan aktual perangkat lunak akuntansi pendekatan technology acceptance model. Jurnal Akuntansi dan Keuangan, 19(2), 67-81. https://doi.org/10.9744/jak.19.2.67-81 Huei, C. T., Cheng, L. S., Seong, L. C., Khin, A. A., & Bin, R. L. (2018). Preliminary study on consumer attitude towards fintech products and services in Malaysia. International Journal of Engineering & Technology, 166-169. Husaini, A. (2020). Lebih efektif lembaga amil zakat siap transformasi ke era digital. Retrieved from https://nasional.kontan.co.id/news/lebih-efektif-lembaga-amil-zakat-siap-transformasi-ke-era-digital Hussin, D. J. (2016). Forecasting patronage factors of islamic credit card as a new e-commerce banking service: An integration of TAM with perceived religiosity and trust. Journal of Islamic Marketing, 7(4), 1-35. https://doi.org/10.1108/JIMA-07-2014-0050 Ichwan, A., & Ghofur, R. A. (2020). Pengaruh technology acceptance model terhadap keputusan muzakki membayar zakat melalui fintech gopay. Jurnal Ilmiah Ekonomi Islam, 6(2), 129-135. http://dx.doi.org/10.29040/jiei.v6i2.1011 IDX. (2021). Realisasi baru 217 persen wapres implementasi zakat 2021 perlu ditingkatkan. Retrieved from https://www.idxchannel.com/syariah/realisasi-baru-217-persen-wapres-implementasi-zakat-2021-perlu-ditingkatkan Inayah, Agriyanto, & Warno. (2018). The role of spirituality in the behavior of sharia bank mobile banking: Evidence from Indonesia. Jurnal Penelitian Sosial Keagamaan, 26(1), 197-224. https://doi.org/10.21580/ws.26.1.2611 Kardiono. (201). Analisis perilaku pengguna layanan internet banking dengan menggunakan pendekatan technology acceptance model dan perceived enjoyment di Surabaya. Petra Business and Management Review, 2(2), 122-139. Karmanto, G. D., & Baskoro, B. D. (2019). Penggunaan platform crowdfunding dalam menyalurkan zakat, infaq, dan shadaqah (ZIS): Studi intensi masyarakat. Jurnal Ekonomi Manajemen, 1-15. https://doi.org/10.46918/point.v2i2.748 Kashif, M., Sarifuddin, S., & Hassan, A. (2015). Charity donation: Intentions and behavior. Marketing and Intelligence & Planning, 33(1), 90-102. https://doi.org/10.1108/MIP-07-2013-0110 katadata. (2021). Indonesia pengguna fintech tertinggi ketiga di dunia. Retrieved from https://katadata.co.id/intannirmala/digital/60d1c95ea19bb/indonesia-pengguna-fintech-tertinggi-ketiga-di-dunia KNEKS. (2019). Insight: Buletin ekonomi syariah 3. Retrieved from https://knks.go.id/storage/upload/1566575768- Lee, S. (2016). User behavior of mobile enterprise applications. KSII Transaction on Internet and Information Systems, 3972-3985. Liebana-Cabanillas, F., Luna, I. R., & Montoro-Rios, F. (2017). Intention to use new mobile payment system: A comparative analysis of sms and nfc payments. Economic Research-Ekonomska Istraživanja, 892-912. Napitupulu, R. M., Lubis, R. H., & Sapna, F. (2021). Perilaku masyarakat dalam menunaikan zakat di masa pandemi covid-19. Jurnal Ilmiah Ekonomi Islam, 7(2), 771-777. http://dx.doi.org/10.29040/jiei.v7i2.2370 Nursaban, Aedy, H., & Gamsir. (2018). Studi perilaku muzakki dalam membayar zakat di Kota Kendari. Jurnal Progres Ekonomi Pembangunan, 1-16. Pikiran Rakyat. (2019). Dana zakat yang dihimpun lewat teknologi digital setiap tahun meningkat. Retrieved from https://www.pikiran-rakyat.com/ekonomi/pr-01320418/dana-zakat-yang-dihimpun-lewat-teknologi-digital-setiap-tahun-meningkat Purwanto, Sulthon, M., & Wafirah, M. (2021). Behavior intention to use online zakat: Application of technology acceptance model with development. ZISWAF: Jurnal Zakat dan Wakaf, 8(1), 44-60. Rahmawaty, A., Kusuma, H., & Sriyana, J. (2010). The role of spiritual motivation in acceptance of information technology in Indonesia. Proceedings of The Second International Workshop in Islamic Economics Theory, 151-169. Rahmiati, & Yuannita, I. I. (2019). The influence of trust, perceived usefulness, perceived ease of use, and attitude on purchase intention. Jurnal Kajian Manajemen Bisnis, 8(1), 27-34. https://doi.org/10.24036/jkmb.10884800 Raksadigiri, M. W., & Wahyuni, S. (2020). Perceived ease of use effect on perceived usefulness and attitude towards use and its impact on behavioural intention to use. International Journal of Advance Research, 8(12), 439-444. http://dx.doi.org/10.21474/IJAR01/12166 Republika. (2019). Digitalisasi zakat dan tantangannya apa saja. Retrieved from https://www.republika.co.id/berita/q0uw4q313/digitalisasi-zakat-dan-tantangannya-apa-saja Rohmah, I. L., Ibdalsyah, & Kosim, A. M. (2020). Pengaruh persepsi kemudahan berdonasi dan efektifitas penyaluran menggunakan fintech crowdfunding terhadap minat membayar zakat, infaq, dan shadaqoh. KASABA: Jurnal Ekonomi Islam, 13(1), 42-51. http://dx.doi.org/10.32832/kasaba.v13i1.3397 Sari, A. P., Anggraini, D., & Zaenardi, A. K. (2020). Menjadi OPZ penyintas di masa pandemi. Jakarta: BAZNAS. Setiawan, R. A., Setyohadi, D. B., & Pranowo. (2017). Understanding customers intention to use social network sites as complaint channel: An analysis of young customers perspectives. The 2nd International Conference on Energy, Environmental and Information System. doi:10.1051/e3sconf/20183111014 Sharma, & Sharma, N. (2016). Relationship between consumers spirituality and green purchasing intentions: the mediation effect of perceived consumer effectiveness. Kozhikode Society and Management Review, 1-11. https://doi.org/10.1177%2F2277975216665694 Siyal, A. W., Donghong, D., Umrani, W. A., Siyal, S., & Bhand, S. (2019). Predicting mobile banking acceptance and loyalty in Chinese bank customers. Sage Publications, 1-21. Solimun. (2002). Structural equation modeling: LISREL dan AMOS. Malang: Universitas Brawijaya. suaramuslim. (2017). Berzakat. Retrieved from https://suaramuslim.net/hukum-zakat-via-online/ Sukmawati, H., Joni, Rasyid, A. F., & Kurniaputri, M. R. (2021). Penerimaan dan penggunaan Layanan mobile banking perbankan syariah: Ekstensi technology acceptance model. Jurnal Ilmiah Ekonomi Islam, 7(3), 1-13. http://dx.doi.org/10.29040/jiei.v7i3.3615 Surendran, P. (2012). Technology acceptance model: A survey of literature. International Journal of Business and Social Research. http://dx.doi.org/10.18533/ijbsr.v2i4.161 Umer, S. A., & Shah, N. (2017). New determinants of ease of use and perceived usefulness for mobile banking adoption. International Journal Electronic Customer Relationship Management, 11(1), 44-67. http://dx.doi.org/10.1504/IJECRM.2017.086751 Wiethoff, C. (2004). Motivation to learn and diversity training: Application of the theory of planned behavior. Human Resource Development Quarterly, 15(3), 263-278. https://psycnet.apa.org/doi/10.1002/hrdq.1103 Wiharjo, B., & Hendratmi, A. (2019). Persepsi penggunaan zakat online di Indonesia. Jurnal Ekonomi Syariah dan Terapan, 6(2), 331-343. https://doi.org/10.20473/vol6iss20192pp331-343